Sign up ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Solve the following equation over the reals:$$ x^3 + 1 = 2\sqrt[3]{{2x - 1}} $$ I noticed that 1 is a trivial solution, then I tried raising the equation to the 3rd, then dividing the polynomial by $(x-1)$.. But I can't see the solution, how do I go from here?

share|cite|improve this question

4 Answers 4

This solution will be frustratingly incomplete, since I'm not seeing an easy way to solve completely by hand. But here is where the road leads...

When solving equations in $x$, it is usually helpful to rewrite it in terms of a polynomial in $x$. To that end, cube both sides to obtain $8(2x-1)=(x^3+1)^3$, which upon moving terms to one side and expanding yields $$x^9+3x^6+3x^3-16x+9=0$$ Noting that $x=1$ is a trivial solution, we see that we can factorize this as $$(x-1)(x^8+x^7+x^6+4x^5+4x^4+4x^3+7x^2+7x-1)=0$$ One can in fact factor this further, though I should confess I only saw this after looking up the roots: $$(x-1)(x^2+x-1)(x^6+2x^4+2x^3+4x^2+2x+9)=0$$ The roots of the first two factors give three real roots which can be found by hand as $x=1,(-1\pm\sqrt{5})/2$. It turns out that the last factor has no real roots, and so these three are the result.

The two incomplete points:

  1. Does anyone know a good way to spot the factor of $x^2+x-1$?
  2. Does anyone see an obvious way to verify the lack of real roots in the last equation?
share|cite|improve this answer
For 2., rewrite it as $x^6+x^4+x^2(x+1)^2+2x^2+(x+1)^2+8$. – Micah Jul 21 '14 at 14:15
$x^2+x-1$ isn't nice factorable. – rae306 Jul 21 '14 at 14:17
It's quadratic, so complete the square and solve. (Also, taking $x\to -x$ turns this into the equation for the golden ratio. So it's not an unfamiliar one.) @RainiervanEs – Semiclassical Jul 21 '14 at 14:19
You actually came up with the 3 correct solutions @Semiclassical, those exactly 3 solutions were published soon after the exam was over. Thank you ! – Victor Jul 21 '14 at 18:32
I've managed to come up with the following solution a few days ago : Given $$2\cdot (2x-1)^\frac13=x^3+1$$, we divide be 2 and denote the RHS as f(x). Further, we notice that the LHS is the inverse of this function and we get f(x)=f^(-1)(x). After proving that both function are monotonous we simplify the last equation to f(x)=x, which further gives us x^3+1-2x=0 . Since 1 is a trivial solution, we divide by (x-1), then take the quadratic solution, yielding the wished result. – Victor Aug 5 '14 at 11:23

We have $$x^3+1=2(2x-1)^{1/3}\iff x^3=2(2x-1)^{1/3} -1.$$ Here, setting $y=(2x-1)^{1/3}$ gives us $$y^3=2x-1 \ \ \text{and}\ \ x^3=2y-1.$$ Hence, we have $$\begin{align}y^3-x^3=(2x-1)-(2y-1)&\Rightarrow (y-x)(y^2+yx+x^2)=2(x-y)\\&\Rightarrow (y-x)(y^2+yx+x^2+2)=0\\&\Rightarrow (y-x)\{(x+(y/2))^2 + (3/4)y^2+2\}=0\\&\Rightarrow y=x.\end{align}$$ Hence, we have $$x^3=2x-1\iff (x-1)(x^2+x-1)=0\iff x=1,\frac{-1\pm\sqrt 5}{2}.$$

share|cite|improve this answer

For $x$ - real $$2\cdot(2x-1)^\frac13=x^3+1$$

Let $y= (2x-1)^\frac13$

Therefore, $$y^3=2x-1$$ $$x=\frac{(y^3+1)}{2}$$

Then you get $$2\cdot y=(\frac{y^3+1}2)^3+1$$

Resolve it for $y$, and then replace find the $x$

Resolving for $y$:

  1. multiply both sides by 8 and you get

$$16\cdot y=(y^3+1)^3+8$$

$$16\cdot y = y^9+ 3\cdot y^6+3\cdot y^3 +9$$

$$(y-1)(y^6 + 2\cdot y^4+ 2\cdot y^3 +4\cdot y^2+2\cdot y+9 )(y^2 + y - 1)=0$$

Then we get: $y-1 = 0$ => $y=1$

$y^2 +y - 1=0$ => $y = \frac{1}{2}(-1\pm \sqrt5)$

$y^6 + 2\cdot y^4+ 2\cdot y^3 +4\cdot y^2+2\cdot y+9 =0$ => No roots

share|cite|improve this answer
how do you plan on solving for $y$? – cirpis Jul 21 '14 at 14:06
$x = \frac{y^3+1}{2}$ – Daniel Fischer Jul 21 '14 at 14:06
As DanielFischer is pointing out, you've got a typo for $x=(y^3+1)/2$ – Semiclassical Jul 21 '14 at 14:11
And I'm skeptical of this approach: while it keeps 1 as a root, the other two irrational roots aren't mapped to anything nice. – Semiclassical Jul 21 '14 at 14:13

$\ \frac{{x^3 + 1}}{2} = \sqrt[3]{{2x - 1}} \ $, denote LHS by $f(x)$ .

Since $f(x)$ is bijective, it must have an inverse function, particularly the RHS in this situation.So, the equation is simplified to $\ f(x) = f^{ - 1} (x) \ $, which further yields $\ f(f(x)) = x \ $. Since both functions are strictly increasing, it would only make sense that $f(x)=x$, therefore $\ x^3 + 1 - 2x = 0 \ $. $x=1$ is a trivial solution so we may rewrite our equation as $\ (x - 1)(x^2 + x - 1) = 0 \ $ .

By solving the quadratic we get $\ x_{1,2} = \frac{{ - 1 \pm \sqrt 5 }}{2} \ $ .We conclude that the real solutions of our equation are comprised by $\ S = \{ 1,\frac{{ - 1 \pm \sqrt 5 }}{2}\} \ $ .

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.